Determinants of Firm Failure: Empirical Evidence from China. (23rd July 2015) - He, Canfei; Yang, Rudai
Abstract: During the economic transition, Chinese industries are highly dynamic, with substantial firm entry and failure. This study investigates the driving forces of firm failure in China. Based on the annual survey of industrial firms during 1998–2007, this study first describes the patterns of firm failure. On average, less productive and older firms are more likely to fail, while firms with governmental supports are more likely to survive. Statistical results based on the linear probability model for panel data indicate that market competition crowds out less productive firms. Competition dominates learning effects and imposes challenges on the survival of older firms. There is an inverted U‐shaped relationship between firm age and firm failure. Local supportive policies such as subsidies and banking loans can reduce the chance of firm failure. Governmental policies also moderate the impact of productivity and firm age on firm failure. The findings from this study enrich the understanding of industrial dynamics in the transitional China.